Assessing the potential tsunami source of the Manila trench at the Bengkayang nuclear power plant site in Kalimantan using topographical details - Sugeng Pribadi; Widjo Kongko; Nurkhalis Rahili; Fauzi Fauzi; Hadi Suntoko; Sapto Nugroho; Sunarko Sunarko; Telly Kurniawan; Euis Etty Alhakim (International Journal of Renewable Energy Development, 2024)
Tsunamis pose a significant threat to the construction of Nuclear Power Plants. Therefore, it is necessary to carry out a comprehensive study regarding the potential threat of tsunamis and mitigation measures using detailed data at prospective locations. This assessment is a prerequisite for effective environmental impact planning and analysis. To determine the suitability of a prospective location, careful consideration of natural factors, including earthquakes as triggers for tsunamis, is essential. The main objective of this tsunami research is to assess the level of safety of potential locations against tsunami hazards and develop appropriate mitigation strategies. This research uses the Cornell Multigrid Coupled Tsunami (COMCOT) tsunami modeling technique. This modeling approach utilizes topographic and bathymetric data obtained through extensive field surveys. In addition, this research aims to determine the maximum tsunami height in the inundation area and identify potential tsunami hazards arising from various scenarios related to the active tectonic potential of the Philippine Manila Trench. The Bengkayang Gosong Beach area and West Kalimantan are among the candidate locations that may be affected with the estimated tsunami height being between 0.48 meters and 0.62 meters. The tsunami arrival time was between 9 hours 10 minutes to 9 hours 24 minutes. These findings play an important role in conducting comprehensive risk assessments for nuclear power plant development, ensuring that necessary steps are taken to reduce potential hazards associated with tsunamis.